Drought and airborne emissions in Dnipropetrovsk region, Ukraine - Kharytonov, Mykola; Харитонов, Микола Миколайович; Lakyda, Petro; Лакида, Петро; Matushevych, Lubov; Матушевич, Любов; Andreiev, Artem; Андрєєв, Артем; Kozlova, Anna; Козлова, Анна; Stankevich, Sergey; Станкевич, Сергій (Taylor & Francis, 2025)
Global heating is upon us and, in Ukraine, drought is exacerbated by the toxic emissions of heavy industry. In 2022–4, compared with 2019–21, the Dnipropetrovsk region of Ukraine experienced an increase of land surface temperature of more than 5°C in the range of >30°C affecting 9 611 km2 (27% of the region). Comparative assessment revealed lands with a very low surface soil moisture fraction < 0.16) across half of the region by the end of the study period. Analysis of leaf area index indicates that regional drought conditions in 2023–2024 are also related to industrial emissions of nitrogen dioxide and sulphur dioxide. Глобальне потепління вже близько, і в Україні посуха посилюється токсичними викидами важкої промисловості. У 2022–2024 роках, порівняно з 2019–2021 роками, у Дніпропетровській області України спостерігалося підвищення температури поверхні землі більш ніж на 5°C у діапазоні >30°C, що торкнулося 9 611 км² (27% території регіону). Порівняльна оцінка земної поверхні виявила дуже низьку частку вологості поверхневого ґрунту (<0,16) на половині території регіону до кінця періоду дослідження. Аналіз індексу листової поверхні показує, що регіональні умови посухи у 2023–2024 роках також пов'язані з промисловими викидами діоксиду азоту та діоксиду сірки.
Посуха та викиди в повітря у Дніпропетровській області, Україна
Keywords: spatial-temporal trends; просторово-часові тенденції; climate change; зміна клімату; airborne emission; викиди в повітря